Political and legal views of Anacharsis and Hellenism (Journal of actual problems of jurisprudence, 2018)
In the article the author analyzes the data on the origin and life of the great Sak philosopher Anacharsis. To analyze the views of Anacharsis about society, state and law the author studied his extant letters. The author refers to information about the Anacharsiss trip to the Greeks to gain experience in the field of law and policy, and his meeting with the great philosopher Solon, about their conversations. In general, according to the author, Hellenism influenced on the development of political and legal views of Anacharsis greatly. Anacharsis largely proud of the fact that he is a free man, in his understanding happiness is a free and independent life from the property. However, after returning to Sak valley Anaharsis was killed for the glorification of the Hellenic values.Key words: saks, Hellenism, political and legal views, thinker.